The Impact of Sustainability Commitments on Corporate Fiscal Policies: An Empirical Analysis of Indonesian Consumer Cyclical Entities - Nola Safira; Wiralestari Wiralestari; Ilham Wahyudi; Enggar Diah Puspa Arum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research investigates how Environmental, Social, and Governance (ESG) practices influence the tax liabilities of consumer cyclical companies in Indonesia between 2020 and 2024. By employing the Effective Tax Rate (ETR) as a proxy for tax burden, the study analyzes 160 data points from 32 purposively selected firms. Utilizing a Fixed Effect Model for panel data regression, the empirical results indicate that superior ESG performance significantly correlates with a higher ETR. This suggests that corporations with higher sustainability transparency tend to exhibit better tax compliance and avoid aggressive tax avoidance schemes. Grounded in stakeholder and legitimacy theories, these findings underscore that ethical ESG adoption strengthens public accountability and enhances the integrity of corporate governance within the Indonesian capital market.